Volatile organic compounds in the atmosphere of Mexico City (2015)
The Mexico City Metropolitan Area (MCMA) is one of the most polluted megacities in North America. Therefore, it is an excellent benchmark city to understand atmospheric chemistry and to implement pilot countermeasures. Air quality in the MCMA is not within acceptable levels, mainly due to high ground levels of ozone (O3). Tropospheric O3 is a secondary pollutant formed from the oxidation of volatile organic compounds (VOCs) in the presence of nitrogen oxides and sunlight. To gain a better understanding of O3 formation in megacities, evaluate the effectiveness of already-implemented countermeasures, and identify new cost-effective alternatives to reduce tropospheric O3 concentrations, researchers and environmental authorities require updated concentrations for a broader range of VOCs. Moreover, in an effort to protect human health and the environment, it is important to understand which VOCs exceed reference safe values or most contribute to O3 formation, as well as to identify the most probable emission sources of those VOCs. In this work, 64 VOCs, including 36 toxic VOCs, were measured at four sites in the MCMA during 2011-2012. VOCs related to liquefied petroleum gas leakages exhibited the highest concentrations. Toxic VOCs with the highest average concentrations were acetone and ethanol. The toxic VOC benzene represented the highest risk to Mexican citizens, and toluene contributed the most to O3 formation. Correlation analysis indicated that the measured VOCs come from vehicular emissions and solvent-related industrial sources. VOC measurements revealed that compounds related to liquefied petroleum gas leakages are the most abundant, the toxic VOC benzene represents the highest risk to citizens, and toluene is the greatest VOC contributor to O3 formation in Mexico City. © 2015 Elsevier Ltd.